2020
DOI: 10.3390/ma13163522
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D Printing Scaffold with Porcine Skin Decellularized Bio-Ink for Soft Tissue Engineering

Abstract: Recently, many research groups have investigated three-dimensional (3D) bioprinting techniques for tissue engineering and regenerative medicine. The bio-ink used in 3D bioprinting is typically a combination of synthetic and natural materials. In this study, we prepared bio-ink containing porcine skin powder (PSP) to determine rheological properties, biocompatibility, and extracellular matrix (ECM) formation in cells in PSP-ink after 3D printing. PSP was extracted without cells by mechanical, enzymatic, and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In terms of mechanical properties and printability, the elastic modulus of Matrigel has been proven to be around 450–650 Pa with different measurement, 55,56 and it is similar to the storage modulus of decellularized skin ECM, 57,58 which can simulate the growth environment of skin‐derived stem cells. Matrigel undergoes gelation at temperatures in the range 22–37°C and presents the shear‐thinning properties, which are desirable for in situ bioprinting because of the continuous and smooth extrusion 59 .…”
Section: Resultsmentioning
confidence: 99%
“…In terms of mechanical properties and printability, the elastic modulus of Matrigel has been proven to be around 450–650 Pa with different measurement, 55,56 and it is similar to the storage modulus of decellularized skin ECM, 57,58 which can simulate the growth environment of skin‐derived stem cells. Matrigel undergoes gelation at temperatures in the range 22–37°C and presents the shear‐thinning properties, which are desirable for in situ bioprinting because of the continuous and smooth extrusion 59 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Lee et al examined the biocompatibility of a bio-ink composed of dECM powder from porcine dermis dissolved in a 2-3% sodium alginate hydrogel, at 10 and 20 mg/ml (Lee et al, 2020). Rheological characterization of the prepared inks showed that ink viscosity could be tuned by varying dECM powder concentration.…”
Section: Design Of Bio-inks For Tissue Engineering and Disease Modelingmentioning
confidence: 99%
“…Next, the ECM-related bioink integrated with endothelial progenitor cells and adipose-derived stem cells was further used to print 3D pre-vascularized skin patch, which significantly promoted in vivo wound re-epithelization and neovascularization. Similarly, Lee et al [ 160 ] developed bio-ink containing decellularized porcine skin powder, which exhibited enhanced printability and biocompatibility for 3D bioprinting.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%